Oxygen, carbon isotope, trace element and foraminifera assemblages from sediment cores collected in Western Norwegian fjords - Mattia Ferraro; Bjørg Risebrobakken; Irina Polovodova Asteman; Elin Darelius; Amandine Tisserand; Natalya Gallo; Anne Gro Vea Salvanes (PANGAEA, 2025)
Bottom water samples were analysed in Bergen (Norway) using ICP-OES (Inductively Coupled Plasma - Optical Emission Spectrometry) Agilent Technologies, 720 to measure oxygen in seawater (both units: ml/l and umol/kg) and trace elements (Mn, Ca and Mn/Ca ratio). The D13C of bottom waters was analysed using a Thermo Scientific Gasbench connected to a Thermo Scientific Delta V+ isotope ratio mass spectrometer. The surface sediment samples (0-1 cm) from cores KB22-237-01MC-D, KB22-237-02MC-F, KB22-237-03MC-C, KB22-237-04MC-D, KB22-237-05MC-C, KB22-237-06MC-F, KB22-237-07MC-E, KB22-237-10MC-D and KB22-237-11MC-D were washed through a 63 μm sieve and then the benthic foraminifera (both stained and dead assemblages) were collected with a standard stereo-microscope. We calculate the total number of individuals present in the samples (dead + alive), the relative abundance (%), the number of species in the samples and the Calcareous/Agglutinated species ratio. We also calculate the diversity indices Shannon-Wiener index, Simpson 1-D index, dominance index and Hulberts index using PAST software.
In: Ferraro, M et al. (2025): Dissolved oxygen concentration, trace elements concentration, carbon isotope composition and foraminifera assemblages data from Western Norwegian fjords [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982538